Synthesis, structure and anticancer activity of two platinacyclic complexes bearing isopropyl eugenoxyacetate and pyridine derivatives - 2 (My University, 2018)
Synthesis, structure and anticancer activity of two platinacyclic complexes bearing isopropyl eugenoxyacetate and pyridine derivatives
Keywords: Kháng ung thư